Plant root mechanisms and their effects on carbon and nutrient accumulation in desert ecosystems under changes in land use and climate - Tariq, Akash (2024)
Deserts constitute the world´s third-largest active carbon (C) reservoir. The survival of desert ecosystems hinges on a suite of adaptations to exceedingly xeric conditions, altering their susceptibility to diverse forms of global change. Comprehending the impacts of environmental change on arid land ecosystem services necessitates a comprehensive understanding of how distinct plant ecophysiological and structural traits respond. This review aims to dissect the mechanisms influencing C and mineral nutrient stocks within deserts, with a specific focus on plant root systems. Moreover, it delves into how these factors are modulated by land use and climate change. The root architecture of desert plant species diverges due to water acquisition strategies that have evolved over extended periods, contingent upon temporal and spatial water availability. Plants with different root architectures influence plant biomass; therefore, C and nutrient stocks are closely linked to the overall biomass of plants and their distribution among different organs. Climatic variables hold the potential to reshape the distribution and structure of plant communities, thereby potentially diminishing C and nutrient stocks within plant-soil systems. For instance, intense droughts can adversely impact shallow-rooted plants´ root development, photosynthesis, nutrient uptake, and survival rate. Even deep-rooted plants can face the consequences if the groundwater level drops. Similarly, practices related to vegetation management exert pronounced effects on plant communities, soil composition, root-associated microorganisms, root architectures, biomass, and plant nutritional status. For instance, high grazing pressure significantly impacts shallow-rooted plants more than deep-rooted ones, but overall, C and nutrient stocks decrease due to biomass reduction, and long-term overgrazing practices can even alter the community structure. Thus, shallow-rooted plants are more vulnerable to climate change and human interference than deep-rooted ones in desert ecosystems. In-depth investigations into root architecture and deep soil layers are crucial for enhancing our mechanistic understanding of this intricate system and facilitating strategic management. Data analysis clearly shows that avoiding grazing and harvesting or maintaining them at moderate levels, and even some moderate fertilization, should be generally considered for plant-soil conservation and restoration as adequate management strategies in arid lands. Furthermore, the adoption of socio-ecological approaches to restore degraded communities can safeguard and enable sustainable management of native vegetation. This approach maximizes the retention capacity of C and nutrient stocks within plant-soil systems, mitigates the further expansion of desert regions, and curbs CO2 emissions. This review sheds light on the ongoing imperative to uncover the intricacies of belowground plant-related processes and their pivotal role in shaping the dynamic landscape of desert ecosystems.